2009
DOI: 10.1523/jneurosci.3177-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal Interactions during Learning, Memory Processing, and Decision Making

Abstract: This mini-symposium aims to integrate recent insights from anatomy, behavior, and neurophysiology, highlighting the anatomical organization, behavioral significance, and information-processing mechanisms of corticostriatal interactions. In this summary of topics, which is not meant to provide a comprehensive survey, we will first review the anatomy of corticostriatal circuits, comparing different ways by which "loops" of cortical-basal ganglia circuits communicate. Next, we will address the causal importance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 111 publications
4
132
0
1
Order By: Relevance
“…This dissociation is similar to what is observed in the hippocampus (40). However, differently from the hippocampus, VS manipulations also impair responding to cues in auto-shaping, in Pavlovian-instrumental transfer, or in the early stages of instrumental conditioning, coherently with the high number of reward-responding neurons in this structure but not in the hippocampus (41).…”
Section: Discussionsupporting
confidence: 79%
“…This dissociation is similar to what is observed in the hippocampus (40). However, differently from the hippocampus, VS manipulations also impair responding to cues in auto-shaping, in Pavlovian-instrumental transfer, or in the early stages of instrumental conditioning, coherently with the high number of reward-responding neurons in this structure but not in the hippocampus (41).…”
Section: Discussionsupporting
confidence: 79%
“…In reward memory formation, dopamine, in addition to enabling late-LTP, contributes to offline consolidation processes that continue after a stimulus-stimulus or stimulus-response learning and help better remember the learned association (Shohamy and Adcock, 2010;Wimber et al, 2011). Rodent research revealed that rewarded memories may be spontaneously reactivated during sleep, with a coordinated replay of neuronal activity in the hippocampus and in the striatum during slow-wave sleep Pennartz et al, 2009). Moreover, generation of outcome predictions is proposed to rely on synaptic plasticity mechanisms boosted during slow-wave sleep (SWS) ).…”
Section: Box 2: Role Of Sleep In the Consolidation And Generalizationmentioning
confidence: 99%
“…Striatal dopamine release also plays a role in procedural and reinforcement learning [e.g., [104][105][106][107][108], owing to synaptic plasticity and remodeling. In terms of procedural learning, the Bassociative^portions of the caudate nucleus appear to be involved in early phases of learning, while the Bmotor^puta-men is more prominently engaged when animals execute previously learned movement sequences [109][110][111][112][113][114][115][116][117][118].…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%